THE ROLE OF INSTRUCTIONAL LEADERSHIP, TEACHER EFFICACY, AND COLLABORATIVE PRACTICES IN SHAPING TEACHER DEVELOPMENT AND WELL-BEING: A SYSTEMATIC REVIEW OF CURRENT EDUCATIONAL RESEARCH - Azmi, Nasihin; Musa, Khalip (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This work is a Systematic Literature Review (SLR) about the interrelated roles of instructional leadership, teacher efficacy and collaborative practices in supporting teacher development and well-being. This study seeks to bring together the separate spheres of research on the relationship between leadership, collaboration, and teacher outcomes, acknowledging the critical importance of effective leadership and collaboration in education. Applying the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, a holistic search was performed via Scopus and ERIC databases, which led to the extraction of 28 key pieces of research pertaining to this analysis. Findings are systematically categorized according to three primary themes: (1) instructional leadership and teacher efficacy (2) teacher professional development and collaboration; and (3) broader leadership and education practices. This amalgamation of themes reflects strong interconnections between leadership styles, collaborative efforts, and teacher professional and personal growth. Other than that, it emphasizes that aligned strategies in leadership are essential for redesigning education systems that support teacher performance and well-being. This could also help inform the teachers themselves, helping policymakers, school leaders, and educators to make the most of the investment in teacher development strategies. Finally, they call for additional research to help close the knowledge gaps and increase the practical execution of this knowledge across various educational systems.